Poplars and other fast-growing tree species in Germany: Report of the National Poplar Commission 2020-2023 - Mirko Liesebach; Volker Schneck (Johann Heinrich von Thünen-Institut, 2024)
Every four years, the National Poplar Commissions reports on the progress of the International Poplar Commission IPC, one of the oldest, firmly established organizations of the FAO (Organization for Food and Agriculture of the United Nations). The reports will be collected and published for the 27th session of the International Poplar Commission in Bordeaux in October 2024. For Germany, the Thünen Institute of Forest Genetics is compiling the report on behalf of the Federal Ministry of Food and Agriculture. With the reform of the Poplar Commission, the tree species spectrum was expanded to include also other fast-growing tree species despite poplars and willows. In Germany, in addition to poplars and willows, 12 other tree species are considered fast-growing. Based on the figures from the Federal Forest Inventory (2012), the area of fast-growing tree species is 1.645 million ha. The most common fast-growing tree species is Betula pendula (474 700 ha) followed by Alnus glutinosa (229 250 ha), Larix decidua (223 600 ha), Pseudotsuga menziesii (217 600 ha) and Populus spec. (147 900 ha, incl. willow SRC). The current cultivation of poplars and willows is largely limited to short rotation coppice plantations (SRC). In Germany the total short rotation coppice area is currently stagnating at 6 600 hectares. The factors responsible for this are attractive alternative crops, in particular maize cultivation for biogas, combined with the extensive ban on the conversion of grassland and a lack of impetus from the Greening Regulation passed at EU level. No poplar clones were approved in the reporting period. An extension of the approval was recommended for 4 aspen clones. Furthermore, changes to the approval as basic material for the production of forest reproductive material in the "Tested" category were recommended for several parents of families for the production of hybrid larch progenies. A total of 17 research projects and 38 joint research projects (with together 117 projects) carried out at 60 institutions in Germany on the genetics and breeding, cultivation, physiology, resistance of fast-growing tree species and the harvesting and short-utilization of their wood, as well as on socio-economic and socio-ecological aspects were funded by third parties and have been included in the report. Also, 142 publications are listed in the report. – – Alle vier Jahre berichten die Nationalen Pappelkommissionen über den Entwicklungsfortschritt der Internationalen Pappelkommission IPC, eine der ältesten, festverankerten Organisationen der FAO (Organisation für Ernährung und Landwirtschaft der Vereinten Nationen). Die Berichte werden gesammelt und zur 27. Tagung der Internationalen Pappelkommission in Bordeaux im Oktober 2024 veröffentlicht. Für Deutschland stellt das Thünen-Institut für Forstgenetik im Auftrag des Bundesministeriums für Ernährung und Landwirtschaft den Bericht zusammen. Mit der Reform der Pappelkommission wurde das Baumartenspektrum auf schnellwachsende Baumarten erweitert. In Deutschland werden neben Pappeln und Weiden 12 weitere Baumarten als schnellwachsende betrachtet. Anhand der Zahlen aus der Bundeswaldinventur (2012) ergibt sich eine Fläche mit schnellwachsenden Baumarten von 1,645 Mio. ha. Die häufigste schnellwachsende Baumart ist die Betula pendula (474 700 ha) gefolgt von Alnus glutinosa (229 250 ha), Larix decidua (223 600 ha), Pseudotsuga menziesii (217 600 ha) und Populus spec. (147 900 ha, incl. Weide KUP). Der aktuelle Anbau von Pappeln und Weiden beschränkt sich weitgehend auf Kurzumtriebsplantagen. Die gesamte Kurzumtriebsplantagenfläche stagniert in Deutschland derzeit bei 6 600 Hektar. Dafür verantwortliche Faktoren sind attraktive Alternativkulturen, insbesondere Maisanbau für Biogas, verbunden mit dem weitgehenden Verbot der Umwandlung von Grünland sowie mangelnde Impulse aus der auf EU-Ebene beschlossenen Greening-Verordnung. Im Berichtszeitraum wurden keine Pappelklone zugelassen. Für 4 Aspenklone wurde eine Verlängerung der Zulassung befürwortet. Weiterhin wurden bei mehreren Familieneltern zur Erzeugung von Hybridlärchen-Nachkommenschaften Änderungen in der Zulassung als Ausgangsmaterial zur Erzeugung von forstlichem Vermehrungsgut in der Kategorie 'Geprüft' empfohlen. Siebzehn Forschungsprojekte und 38 Verbundprojekte (mit zusammen 117 Einzelvorhaben) wurden durch Drittmittel an 60 Institutionen in Deutschland zur Genetik und Züchtung, Anbau, Physiologie, Resistenzen von schnellwachsenden Baumarten sowie Ernte und Verwertung ihres Holzes und zu soziökonomischen bzw. -ökologischen Aspekten gefördert. 142 Veröffentlichungen sind im Bericht erfasst.
urn:nbn:de:gbv:253-202404-dn068120-0
Keywords: 630; Populus; Salix; Larix eurolepis; Robinia pseudoacacia; Larix decidua; Quercus rubra; Pseudotsuga menziesii; cultivated area; short rotation coppice; forest reproductive material; research projects; publication; Anbaufläche; Kurzumtriebsplantage; forstliches Vermehrungsgut; Forschungsprojekte; Veröffentlichung